Purification of archetypal soybean root suberin mostly comprising alka(e)noic acids using an ionic liquid catalyst - Escórcio, Rita (2023)
Funding Information: The authors acknowledge CERMAX, ITQB-NOVA, Oeiras, Portugal where the NMR data were acquired with equipment funded by FCT. The authors are thankful to Giovanna Martins for technical support during her BSc internship. Funding Information: Funding from the European Research Council through grant ERC CoG-647928, from the Office of Naval Research Global (ONRG, RESEARCH GRANT—N62909-23-1-2007), and from Fundação para a Ciência e Tecnologia (FCT) by Project MOSTMICRO ITQB with refs UIDB/04612/2020 and UIDP/04612/2020 and LS4FUTURE Associated Laboratory (LA/P/0087/2020). RE is grateful to FCT funding for her PhD scholarship (2021.06435.BD). Publisher Copyright: Copyright © 2023 Escórcio, Sandhu, Bento, Tomé, Moreira, Brözel and Silva Pereira.